Improving sustainability during hospital design and operation : a multidisciplinary evaluation tool - Capolongo, Stefano; Bottero, Marta Carla; Buffoli, Maddalena; Lettieri, Emanuele (Green Energy and Technology, 2015)
This book describes the Sustainable High Quality Healthcare (SustHealth) project, which had the goal of developing an original multidisciplinary evaluation tool that can be applied to assess and improve hospitals' overall sustainability. The comprehensive nature of the appraisal offered by this tool exceeds the scope of most current rating systems, which typically permit a thorough evaluation of relevant environmental factors when designing a new building but fail to consider social and economic impacts of the design phase or the performance of the hospital's operational structure in these fields. The multidisciplinary evaluation system was developed, from its very inception through to its testing, by following a scientific experimental method in which a global perspective was constantly maintained, as opposed to a focus only on specific technical issues. Application of the SustHealth rating tool to a currently functioning hospital, or one under design, will identify weaknesses and guide users to potential low-cost short-term solutions and longer-term strategies for improvement.